Explaining Breast Density Recommendations: An Introductory Workshop for Breast Health Providers - Rachel S. Casas; Ambili Ramachandran; Christine M. Gunn; Janice M. Weinberg; Kitt Shaffer (Association of American Medical Colleges, 2017)
Introduction High breast density is an independent risk factor for breast cancer and can decrease the sensitivity of mammography. However, evidence surrounding recommendations for patient risk stratification and supplemental screening is evolving, and providers receive limited training on breast density counseling. Methods We implemented an introductory, interactive workshop about breast density including current evidence behind supplemental screening and risk stratification. Designed for providers who counsel women on breast health, this workshop was evaluated with internal medicine providers, primary care residents, and radiology residents. We surveyed participants about knowledge and attitudes at baseline, postintervention (residents and providers), and 3-month follow-up (providers only). We compared baseline and postintervention scores and postintervention and 3-month follow-up scores using paired t tests and McNemar's tests. Results Internal medicine providers had significant gains in knowledge when comparing baseline to postintervention surveys (6.5-8.5 on a 10-point scale, p < .0001), with knowledge gains maintained when comparing postintervention to 3-month follow-up surveys (p = .06). Primary care and radiology residents also had significant gains in knowledge when comparing baseline to postintervention surveys (p < .004 for both). All learner groups reported increases in their confidence regarding counseling women about breast density and referring for supplemental screening. Discussion Through this breast density session, we showed trends for increased knowledge and change in attitudes for multiple learner groups. Because we aim to prepare providers with the best currently available recommendations, these materials will require frequent updating as breast density evidence and national consensus evolve.